Lithium iron manganese phosphate positive electrode material, preparation method and application thereof
Patent Information
- Application Number
- CN202611240415.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-09-25
AI Technical Summary
(1)本发明利用磷酸锰铁锂表面硅酸盐和残余碳酸锂反应生成锂-硅酸盐,简化了工艺流程,生成的锂-硅酸盐为锂离子导体,其晶体结构中存在可供Li+快速迁移的三维通道,能够显著降低正极材料与电解液之间的界面阻抗,提高电池的倍率性能。
Smart Images

Figure CN122822753A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery materials, and relates to a cathode material, specifically a lithium iron manganese phosphate cathode material and its preparation method and application. Background Technology
[0002] Lithium manganese iron phosphate (LiMn) 1-x Fe x Lithium manganese phosphate (LMFP), as an upgraded alternative to lithium iron phosphate, combines the high safety of lithium iron phosphate with the high voltage advantage of lithium manganese phosphate. Its theoretical energy density is 15-20% higher than that of lithium iron phosphate, making it an important development direction for next-generation power battery cathode materials. However, the commercial application of lithium manganese iron phosphate still faces two major technological bottlenecks: First, it has poor electrical conductivity. Lithium manganese iron phosphate is an insulating material, and its electronic conductivity (10⁻⁶) is low. -10 S / cm) and lithium-ion diffusion coefficient (10 -15 cm 2 The low ratio ( / s) severely restricts the rate performance and low-temperature performance of the material.
[0003] Secondly, there is the issue of manganese leaching. During charging and discharging, Mn... 3+ The distortion caused by the Jahn-Teller effect leads to the dissolution of manganese ions from the crystal lattice into the electrolyte, resulting in material structure degradation and capacity decay. This is the core issue limiting the cycle life of lithium manganese iron phosphate. Summary of the Invention
[0004] In view of the defects and deficiencies of the existing technology, the present invention provides, firstly, a lithium iron manganese phosphate cathode material; secondly, a method for preparing the lithium iron manganese phosphate cathode material; and thirdly, a battery.
[0005] In a first aspect, the present invention provides a lithium iron manganese phosphate cathode material, comprising a substrate, a first coating layer, and a second coating layer, wherein the substrate has the general chemical formula LiFe. 1-x-y Mn x M y PO4, 0.5≤x≤0.9, 0.02≤y≤0.05, M is any one or more of W, Mo, Nb, V, Ti, and Zr; The first coating layer covers at least a portion of the surface of the substrate, and the first coating layer is carbon. The second coating layer covers at least a portion of the surface of the particles formed by the matrix and the first coating layer, and the second coating layer is any one or more of magnesium metasilicate and magnesium aluminum silicate.
[0006] Preferably, the mass ratio of the first coating layer to the substrate is (1.0%~2.0%):1.
[0007] Preferably, the mass ratio of the second coating layer to the substrate is (0.5%~5%):1.
[0008] Secondly, the present invention provides a method for preparing lithium iron manganese phosphate cathode material, comprising the following steps: Step 1: Mix manganese iron phosphate, lithium source, M cation source, deionized water and carbon source, and mill to obtain a mixture; Step 2: Spray dry the mixture to obtain precursor powder; Step 3: Heat-treat the precursor powder under an inert atmosphere to obtain cation-doped lithium manganese iron phosphate material. Step 4: Disperse the cation-doped lithium manganese iron phosphate material in deionized water to obtain a suspension; Step 5: Add magnesium salt or aluminum salt to the suspension, then add sodium silicate solution dropwise, and simultaneously add ammonia water. Stir, settle, wash, and vacuum dry to obtain the lithium iron manganese phosphate cathode material.
[0009] Thirdly, the present invention provides a battery comprising the lithium iron manganese phosphate cathode material described in the first aspect or the lithium iron manganese phosphate cathode material prepared by the preparation method described in the second aspect.
[0010] Compared with the prior art, the present invention has the following significant advantages: (1) This invention utilizes the reaction of surface silicates of lithium manganese iron phosphate and residual lithium carbonate to generate lithium-silicate, simplifying the process. The generated lithium-silicate is a lithium-ion conductor, and its crystal structure contains elements that can be used for lithium ion exchange. + The rapidly migrating three-dimensional channels can significantly reduce the interfacial impedance between the cathode material and the electrolyte, thereby improving the rate performance of the battery.
[0011] (2) The silicate coating actively captures dissolved Mn through chemical reaction. 2+ This invention offers a more durable and effective inhibition effect than traditional physical isolation coatings. Experimental data shows that the manganese leaching of the material can be reduced by more than 60%, and the cycle life is significantly extended.
[0012] (3) The preparation method provided by the present invention is highly compatible with the existing lithium manganese iron phosphate production line. Only the silicate composite and sintering steps need to be added. No new complex equipment is required, and it is easy to promote industrialization. Attached Figure Description
[0013] Figure 1 The image shows the XRD pattern of lithium iron manganese phosphate prepared in Example 1. Figure 2This is a SEM image of lithium iron manganese phosphate prepared in Example 1. Detailed Implementation
[0014] The present invention provides the following specific technical solutions.
[0015] In a first aspect, the present invention provides a lithium iron manganese phosphate cathode material, comprising a substrate, a first coating layer, and a second coating layer, wherein the substrate has the general chemical formula LiFe. 1-x-y Mn x M y PO4, 0.5≤x≤0.9, 0.02≤y≤0.05, M is any one or more of W, Mo, Nb, V, Ti, and Zr; The first coating layer covers at least a portion of the surface of the substrate, and the first coating layer is carbon. The second coating layer covers at least a portion of the surface of the particles formed by the matrix and the first coating layer, and the second coating layer is any one or both of magnesium metasilicate and magnesium aluminum silicate.
[0016] Research has shown that using a high-manganese doped matrix with multi-element co-doping of tungsten, molybdenum, niobium, vanadium, titanium, and zirconium allows for precise control of the lattice parameters of lithium iron manganese phosphate (LMP). This not only broadens the lithium-ion insertion / extraction channels within the crystal and reduces bulk ion migration impedance, but also constrains lattice distortion during charge and discharge, enhancing the material's structural stability. The inner carbonaceous first coating layer constructs a continuous conductive network on the particle surface, compensating for the poor intrinsic electronic conductivity of LMP and significantly improving electron conduction rate. The outer magnesium metasilicate and magnesium aluminum silicate second coating layer physically prevents the electrolyte from directly contacting the active matrix, inhibiting the dissolution of manganese and iron transition metal ions and reducing performance degradation caused by electrolyte side reactions. Furthermore, it possesses basic lithium-ion conductivity due to its crystal structure. The interstitial spaces of the magnesium metasilicate chain structure allow for lithium-ion migration, while the layered structure of the magnesium aluminum silicate utilizes interlayer voids for lithium-ion insertion / extraction, enabling slow lithium-ion penetration through the coating layer. However, pure magnesium aluminum silicate still has a significant hindering effect on lithium-ion transport, which can easily drag down rate performance. To address this, a secondary heat treatment is used to induce a solid-phase interface reaction between the outer silicate layer and the residual lithium carbonate on the particle surface, generating lithium-doped magnesium aluminum silicate and lithium magnesium silicate fast ion conductors in situ. By relying on a large number of newly added lithium vacancies in the crystal lattice, the impedance of lithium-ion migration across the coating layer is significantly reduced, thus eliminating the side effects of ion transport resistance caused by silicate coating and further optimizing lithium-ion conduction kinetics.
[0017] The aforementioned matrix doping modification, inner carbon coating for electronic conduction, and outer silicate protection with in-situ derivation of fast ion phases work synergistically to improve rate performance while maintaining long-cycle capacity retention, ultimately producing lithium iron manganese phosphate cathode material with excellent rate performance and ultra-long cycle life.
[0018] Preferably, the mass ratio of the first coating layer to the substrate is (1.0%~2.0%):1.
[0019] Preferably, the mass ratio of the second coating layer to the substrate is (0.5%~5%):1.
[0020] Research has shown that by controlling the ratio of the total mass of the coating layer to the mass of the substrate within the range of (0.5%~5%):1, the inner carbon coating can form a continuous and complete conductive network on the surface of the substrate particles, effectively compensating for the shortcoming of the low intrinsic electronic conductivity of lithium iron manganese phosphate materials. The outer magnesium metasilicate and magnesium aluminum silicate coating layers can uniformly cover the particle surface, stably blocking electrolyte erosion and inhibiting the dissolution of transition metal ions. This total coating amount can fully utilize the dual effects of carbon layer conductivity enhancement and silicate coating interface protection, without blocking lithium ion transport channels or reducing the proportion of active material due to excessive coating content. While ensuring the rate performance and cycle stability of the material, it avoids unnecessary decay of active capacity, achieving the optimal balance between electrochemical performance and active material utilization.
[0021] Secondly, the present invention provides a method for preparing lithium iron manganese phosphate cathode material, comprising the following steps: Step 1: Mix manganese iron phosphate, lithium source, M cation source, deionized water and carbon source, and mill to obtain a mixture; Step 2: Spray dry the mixture to obtain precursor powder; Step 3: Heat-treat the precursor powder under an inert atmosphere to obtain cation-doped lithium manganese iron phosphate material. Step 4: Disperse the cation-doped lithium manganese iron phosphate material in deionized water to obtain a suspension; Step 5: Add metal salt to the suspension and heat in a water bath, then add sodium silicate solution dropwise and simultaneously add ammonia water for stirring and reaction, then let it settle, wash and vacuum dry in sequence to obtain the intermediate product; Step 6: Heat-treat the intermediate product under an inert atmosphere to obtain the lithium iron manganese phosphate cathode material.
[0022] Research has shown that this invention first achieves atomic-level uniform dispersion of each component through co-milling and spray drying of raw materials, followed by in-situ lattice doping of high-valence cations and simultaneous formation of a carbon conductive network via a single inert sintering process. Simultaneously, it fully utilizes the reaction of silicates on the surface of lithium manganese iron phosphate with residual lithium carbonate to generate lithium-silicates in situ. This simplifies the process, eliminates the need for additional lithium source modification, and endows the material with excellent lithium-ion conductivity, significantly reducing interfacial impedance and greatly improving rate performance. Subsequently, magnesium / aluminum metal salts and sodium silicate are precipitated in the liquid phase to uniformly form a magnesium silicate or magnesium aluminum silicate coating layer on the particle surface. A second low-temperature inert heat treatment ensures the coating layer is dense and complete, effectively isolating the substrate from electrolyte corrosion and inhibiting metal ion dissolution, further enhancing structural stability and cycle life. This invention comprehensively optimizes the material's electronic conduction and ion transport capabilities through lattice doping modification, in-situ fast ion construction of lithium silicates, and synergistic modification via double-layer coating. The entire process is simple to operate, uses readily available raw materials, and offers strong controllability, making it suitable for large-scale mass production.
[0023] Preferably, in step 1, the lithium source is any one or more of lithium carbonate, lithium hydroxide, and lithium oxalate; the M element in the M cation source is any one or more of W, Mo, Nb, V, Ti, and Zr; the M cation source is a metal oxide; and the carbon source is any one or more of glucose, sucrose, and citric acid.
[0024] Preferably, in step 1, the ratio of the sum of the molar amounts of manganese and iron in ferromanganese phosphate to the molar amount of lithium in the lithium source is 1: (1.02~1.08).
[0025] Preferably, in step 1, the molar ratio of element M in the M cation source to element lithium in the lithium source is (2%~5%):1.
[0026] Research has shown that within the above-mentioned preferred range, sufficient M high-valence cations can be used to introduce lattice vacancies and strengthen the olivine framework, thereby fully leveraging the effects of increasing the rate of increase and suppressing metal dissolution. At the same time, excessive doping can avoid problems such as impurities and capacity decay, thus balancing electrochemical performance and material purity.
[0027] Preferably, in step 1, the mass ratio of carbon source to manganese iron phosphate is (5%~20%):1.
[0028] Research has shown that within the range of carbon source additions mentioned above, a continuous and uniform conductive network can be constructed on the particle surface, significantly improving the material's electronic conductivity without introducing excessive inert carbon, thus achieving both excellent rate performance and high energy density.
[0029] Preferably, in step 1, the solid content in the mixture is 20wt%~40wt%.
[0030] Preferably, in step 2, during spray drying, the inlet air temperature is 180~220℃ and the outlet air temperature is 100~120℃.
[0031] Preferably, in step 3, the heat treatment temperature is 600~750℃ and the heat treatment time is 8~24h.
[0032] Research has shown that under the above-mentioned optimized heat treatment conditions, the lithiation reaction can be fully carried out, high-valence cations can be uniformly doped into the crystal lattice to form a stable olivine phase with moderate grain size, and organic matter can be fully pyrolyzed to form a continuous conductive carbon layer, thus taking into account both excellent crystal structure integrity and conductivity.
[0033] Preferably, in step 3, the heating rate is 2~5℃ / min.
[0034] Preferably, in step 3, after obtaining the cation-doped lithium manganese iron phosphate material, the process further includes crushing and sieving.
[0035] In actual production, the particle size of lithium manganese iron phosphate after crushing and sieving can be adjusted according to actual needs. Usually, the crushed lithium manganese iron phosphate is passed through a 300-mesh vibrating screen, and the undersize material obtained can meet the industry requirements.
[0036] Preferably, in step 4, the solid content of the suspension is 10 wt.% to 25 wt.%.
[0037] Preferably, in step 5, the metal salt is any one or two of magnesium salts and aluminum salts.
[0038] Further preferred, the magnesium salt is any one or more of magnesium sulfate, magnesium chloride, and magnesium nitrate; the aluminum salt is any one or more of aluminum sulfate, aluminum chloride, and aluminum nitrate.
[0039] Further preferred, in step 5, when magnesium salt and aluminum salt are added simultaneously, the molar ratio of Mg in magnesium salt to Al in aluminum salt is (4.5~5):1.
[0040] Research has shown that the modification effect is better when Mg and Al are coated at the same time. Magnesium can build smooth lithium-ion transport channels, while aluminum can improve the density of the coating layer. The two complement each other. A single magnesium silicate coating layer has a loose structure and poor resistance to electrolyte corrosion, while a single aluminum silicate coating layer has high ion conduction resistance. Magnesium-aluminum composite coating can make up for the defects of the two single coating materials at the same time.
[0041] Within the range of the above-mentioned preferred magnesium and aluminum salts, sufficient magnesium content can improve the lithium-ion conductivity of the coating layer, while a small amount of aluminum can optimize the density of the coating layer and prevent electrolyte corrosion. If the proportion is too low and the aluminum content is too high, it will block the ion channels and increase the impedance. If the proportion is too high and the magnesium content is too large, the coating layer will be loose and easily corroded by the electrolyte. This ratio can form a dense magnesium-aluminum silicate composite coating layer with excellent ion conductivity, taking into account both interface stability and rate performance.
[0042] Preferably, in step 5, the amount of metal salt added is controlled so that the theoretical mass of the silicate coating layer is 0.5 wt.% to 5 wt.% of the mass of the cation-doped lithium manganese iron phosphate.
[0043] Preferably, in step 5, the water bath heating temperature is 65~85℃.
[0044] Research has shown that water bath heating can achieve uniform and stable temperature in the reaction system and a gradual temperature rise, avoiding local overheating that could cause instantaneous and violent hydrolysis of sodium silicate, and preventing magnesium aluminum silicate from agglomerating and precipitating out separately and failing to uniformly coat the matrix.
[0045] Preferably, in step 5, the equivalent silica mass fraction in the sodium silicate solution is 5 wt.%~10 wt.%; and the dropping rate of the sodium silicate solution is 0.5~2 mL / min.
[0046] Research has shown that slowly controlling the dropping rate of sodium silicate solution can maintain the silicate ion concentration in the system at a low level, avoiding the rapid self-aggregation of silicate ions into free silicate particles. This ensures that silicate ions co-precipitate slowly and synchronously with magnesium and aluminum ions in the system, depositing uniformly layer by layer on the surface of the doped lithium manganese iron phosphate substrate to form a thin, continuous, and complete coating layer. If the dropping rate is too fast, the local silicate concentration will increase sharply, resulting in a large number of independent magnesium and aluminum silicate impurities that cannot be uniformly attached to the substrate. This leads to problems such as coating leakage and excessively thick coating in some areas, increasing the lithium ion transport impedance and significantly weakening the coating modification effect. This low-speed dropping range can precisely control the precipitation reaction rate, achieving a uniform, dense, and controllable coating layer, effectively improving the material interface stability and rate performance.
[0047] Preferably, in step 5, when adding sodium silicate solution, ammonia water is added simultaneously to maintain the pH value of the reaction system at 7.0~9.0, and the reaction is continuously stirred for 1~4 hours.
[0048] Research has shown that within the aforementioned optimal pH range, the silicate hydrolysis rate can be stably controlled, allowing magnesium and aluminum ions to slowly and uniformly co-deposit with silicate ions on the substrate surface. Combined with thorough stirring, this ensures that the precipitation reaction proceeds fully, resulting in a complete, uniform, and leak-free coating. This not only isolates the electrolyte and reduces interfacial side reactions but also ensures smooth lithium ion conduction, effectively improving the material's cycle stability and rate performance.
[0049] Preferably, in step 5, the filter cake is allowed to settle at room temperature for 15-30 minutes, the supernatant is poured off, the precipitate is collected, washed 2-4 times with anhydrous ethanol, and then washed 2-4 times with deionized water. The washed filter cake is then placed in a vacuum drying oven and dried at 80-120°C for 10-15 hours.
[0050] Preferably, in step 6, the heat treatment temperature is 450~650℃ and the heat treatment time is 2~6h.
[0051] Research has shown that heat treatment under the above-mentioned optimal conditions can fully remove residual moisture and hydroxyl groups from the coating layer, allowing the magnesium silicate and magnesium aluminum silicate coating layers to crystallize completely, have a dense structure, and retain unobstructed lithium-ion conduction channels. This maximizes the role of the coating layer in passivating the interface and inhibiting metal dissolution without damaging the internal doped and modified lithium manganese iron phosphate matrix crystal structure, while taking into account both the material's ionic conductivity and long-term cycling stability.
[0052] Preferably, in step 6, the heating rate is 1~3℃ / min.
[0053] Preferably, step 6 is followed by cooling, crushing, and sieving, and the undersize material is the finished lithium iron manganese phosphate cathode material.
[0054] Thirdly, the present invention provides a battery comprising the lithium iron manganese phosphate cathode material described in the first aspect or the lithium iron manganese phosphate cathode material prepared by the preparation method described in the second aspect.
[0055] To make the technical problems, technical solutions and technical advantages of the present invention clearer, a detailed description will be given below with reference to specific examples. However, the scope of protection of the present invention is not limited to the following specific embodiments.
[0056] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of the invention.
[0057] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.
[0058] Example 1: A method for preparing a lithium iron manganese phosphate cathode material includes the following steps: Step 1, Precursor Mixing and Milling: Weigh 1000g of manganese iron phosphate (Mn) 0.6 Fe 0.4PO4, 195g lithium carbonate, 17.7g niobium pentoxide (Nb2O5) and 80g glucose as carbon sources were added, along with 3000mL deionized water. The mixture was then fed into a sand mill for grinding to obtain a uniform slurry. Step 2, spray drying: The mixed slurry obtained in Step 1 is spray dried with an inlet air temperature of 200°C and an outlet air temperature of 100°C to obtain precursor powder. Step 3: Place the precursor powder in a tube furnace under a nitrogen atmosphere and heat it to 680°C at a heating rate of 3°C / min. Hold the temperature at this temperature for 12 hours. After natural cooling, pulverize the powder and pass it through a 300-mesh sieve to obtain the matrix material. Step 4: Take 100g of the matrix obtained in Step 3, disperse it in 500mL of deionized water, and stir until uniform to obtain a suspension; Step 5: Add 3.45g magnesium chloride hexahydrate and 0.91g aluminum chloride hexahydrate to the suspension and stir continuously until completely dissolved; add 25mL sodium silicate solution at a dropping rate of 1mL / min, the equivalent silica mass fraction of the sodium silicate solution being 10wt.%; while adding the sodium silicate solution, slowly add 5% ammonia water to maintain the pH of the reaction system at 8.5±0.2, and stir continuously for 2h under a 70℃ water bath; after the reaction is completed, let it stand at room temperature for 20min to settle, pour off the supernatant to collect the precipitate; wash three times with anhydrous ethanol and three times with deionized water, filter, and place the filter cake in a vacuum drying oven at 100℃ for 12h to obtain the coated intermediate product; Step 6, Secondary inert heat treatment: The intermediate product dried in Step 5 is placed in a nitrogen atmosphere furnace and heated to 550℃ at a heating rate of 2℃ / min, and held at that temperature for 4 hours; after cooling in the furnace, it is pulverized and sieved to obtain Nb. 5+ A modified lithium manganese iron phosphate cathode material doped with magnesium aluminum silicate and coated with manganese iron phosphate.
[0059] Figure 1 The image shows the XRD pattern of lithium iron manganese phosphate prepared in Example 1. Figure 1 It can be seen that the main peak of the sample has a high degree of matching with the standard PDF card of lithium manganese iron phosphate, and the crystal is a highly crystalline olivine-type pure phase structure. In addition to the characteristic diffraction peak of lithium manganese iron phosphate, a weak new diffraction peak appears at 2θ=31.2°, which belongs to the lithium-doped magnesium aluminum silicate phase. This result confirms that during the secondary inert atmosphere heat treatment, the outer magnesium aluminum silicate coating precursor undergoes a solid-phase interface reaction with the residual lithium carbonate on the substrate surface, generating a lithium silicate fast ion conductor phase in situ. This achieves chemical bonding between the coating layer components and the substrate interface, which can effectively improve the lithium-ion interfacial conductivity.
[0060] Figure 2 Here is a SEM image of lithium iron manganese phosphate prepared in Example 1. Figure 2As can be seen, the lithium iron manganese phosphate cathode material prepared in Example 1 has a relatively uniform particle size distribution, with no obvious oversized particles or severe agglomeration, and the primary grain size is small. The particle surface is uniformly coated with a coating material, with a regular morphology. The loosely packed structure can provide sufficient channels for the electrolyte to fully wet the particles, shortening the lithium ion diffusion path. The uniform and complete surface coating layer can effectively isolate the electrolyte from direct contact with the active substrate, inhibiting the dissolution of transition metal ions during charging and discharging. At the same time, the fine and uniform particle morphology can improve the material's compaction density and reactivity, which is beneficial to improving the cathode material's rate charge and discharge capability and long-cycle structural stability.
[0061] Example 2: A method for preparing a lithium iron manganese phosphate cathode material includes the following steps: Step 1, Precursor Mixing and Milling: Weigh 1000g of manganese iron phosphate (Mn) 0.6 Fe 0.4 PO4, 195g lithium carbonate, 83.1g tungstic acid and 120g glucose as carbon sources, 3000mL deionized water, mixed and then sent to a sand mill for grinding to obtain a uniform slurry; Step 2, spray drying: The mixed slurry obtained in Step 1 is spray dried with an inlet air temperature of 200°C and an outlet air temperature of 100°C to obtain precursor powder. Step 3: Place the precursor powder in a tube furnace under a nitrogen atmosphere and heat it to 600°C at a heating rate of 3°C / min. Hold the temperature at this temperature for 10 hours. After natural cooling, pulverize the powder and pass it through a 300-mesh sieve to obtain the matrix material. Step 4: Take 100g of the matrix obtained in Step 3, disperse it in 500mL of deionized water, and stir until uniform to obtain a suspension; Step 5: Add 2.91g magnesium sulfate heptahydrate and 0.72g aluminum sulfate octahydrate to the suspension and stir continuously until completely dissolved; add 15mL sodium silicate solution at a dropping rate of 1mL / min, the equivalent silica mass fraction of the sodium silicate solution being 10wt.%; after the addition is complete, slowly add 5% ammonia water to adjust the pH of the system to 8.2±0.2, and stir continuously for 3h under a 60℃ water bath; after the reaction is complete, allow it to settle at room temperature for 20min, pour off the supernatant to collect the precipitate; wash 4 times with anhydrous ethanol and 4 times with deionized water, filter, and place the filter cake in a vacuum drying oven at 100℃ for 12h to obtain the coated intermediate product; Step 6, Secondary inert heat treatment: The intermediate product dried in Step 5 is placed in a nitrogen atmosphere furnace and heated to 650℃ at a heating rate of 2℃ / min, and held at that temperature for 2 hours; after cooling in the furnace, it is pulverized and sieved to obtain W. 6+ A modified lithium manganese iron phosphate cathode material doped with magnesium aluminum silicate and coated with manganese iron phosphate.
[0062] Example 3: A method for preparing a lithium iron manganese phosphate cathode material includes the following steps: Step 1, Precursor Mixing and Milling: Weigh 1000g of manganese iron phosphate (Mn) 0.6 Fe 0.4 PO4, 195g lithium carbonate, 28.73g molybdenum trioxide (MoO3) and 180g glucose were added as carbon sources, 2500mL deionized water was added, and the mixture was sent to a sand mill for grinding to obtain a uniform slurry. Step 2, spray drying: The mixed slurry obtained in Step 1 is spray dried with an inlet air temperature of 200°C and an outlet air temperature of 100°C to obtain precursor powder. Step 3: Place the precursor powder in a tube furnace under a nitrogen atmosphere and heat it to 750°C at a heating rate of 3°C / min. Hold the temperature at this temperature for 8 hours. After natural cooling, pulverize the powder and pass it through a 300-mesh sieve to obtain the matrix material. Step 4: Take 100g of the matrix obtained in Step 3, disperse it in 500mL of deionized water, and stir until uniform to obtain a suspension; Step 5: Add 2.48 g of magnesium sulfate heptahydrate to the suspension and stir continuously until completely dissolved; add 17 mL of sodium silicate solution at a dropping rate of 1 mL / min, the sodium silicate solution having an equivalent silica mass fraction of 10 wt.%; after the addition is complete, slowly add 5% ammonia water to adjust the pH of the system to 8.2 ± 0.2, and stir continuously for 3 h under a 60℃ water bath; after the reaction is complete, allow to settle at room temperature for 20 min, pour off the supernatant to collect the precipitate; wash 4 times with anhydrous ethanol and 4 times with deionized water, filter, and place the filter cake in a vacuum drying oven, and dry at a constant temperature of 100℃ for 12 h to obtain the coated intermediate product; Step 6, Secondary inert heat treatment: The intermediate product dried in Step 5 is placed in a nitrogen atmosphere furnace and heated to 600℃ at a heating rate of 2℃ / min, and held at that temperature for 2 hours; after cooling in the furnace, it is pulverized and sieved to obtain Mo. 6+ Magnesium metasilicate-coated modified lithium manganese iron phosphate cathode material.
[0063] Comparative Example 1: A method for preparing a lithium iron manganese phosphate cathode material includes the following steps: Step 1, Precursor Mixing and Milling: Weigh 1000g of manganese iron phosphate (Mn) 0.6 Fe 0.4 PO4, 195g of lithium carbonate, and 3000mL of deionized water were added, mixed, and then ground in a sand mill to obtain a uniform slurry. Step 2, spray drying: The mixed slurry obtained in Step 1 is spray dried with an inlet air temperature of 200°C and an outlet air temperature of 100°C to obtain precursor powder. Step 3: Place the precursor powder in a tube furnace under a nitrogen atmosphere and heat it to 680°C at a heating rate of 3°C / min. Hold the temperature at this temperature for 12 hours. After natural cooling, pulverize the powder and pass it through a 300-mesh sieve to obtain the cathode material.
[0064] Comparative Example 2: A method for preparing a lithium iron manganese phosphate cathode material includes the following steps: Step 1, weigh 1000g of manganese iron phosphate (Mn). 0.6 Fe 0.4 PO4, 195g of lithium carbonate, 17.7g of niobium pentoxide (Nb2O5), and 3000mL of deionized water were added. After mixing, the mixture was sent to a sand mill for grinding to obtain a uniform slurry. Step 2, spray drying: The mixed slurry obtained in Step 1 is spray dried with an inlet air temperature of 200°C and an outlet air temperature of 100°C to obtain precursor powder. Step 3: Place the precursor powder in a tube furnace under a nitrogen atmosphere and heat it to 680°C at a heating rate of 3°C / min. Hold the temperature at this temperature for 12 hours. After natural cooling, pulverize the powder and pass it through a 300-mesh sieve to obtain the cathode material.
[0065] Comparative Example 3: A method for preparing a lithium iron manganese phosphate cathode material includes the following steps: Step 1, Precursor Mixing and Milling: Weigh 1000g of manganese iron phosphate (Mn) 0.6 Fe 0.4 PO4, 195g lithium carbonate, 17.7g niobium pentoxide (Nb2O5) and 80g glucose as carbon sources were added, along with 3300mL deionized water. The mixture was then fed into a sand mill for grinding to obtain a uniform slurry. Step 2, spray drying: The mixed slurry obtained in Step 1 is spray dried with an inlet air temperature of 200°C and an outlet air temperature of 100°C to obtain precursor powder. Step 3: Place the precursor powder in a tube furnace under a nitrogen atmosphere and heat it to 680°C at a heating rate of 3°C / min. Hold the temperature at this temperature for 12 hours. After natural cooling, pulverize the powder and pass it through a 300-mesh sieve to obtain the cathode material.
[0066] Comparative Example 4: A method for preparing a lithium iron manganese phosphate cathode material includes the following steps: Step 1, Precursor Mixing and Milling: Weigh 1000g of manganese iron phosphate (Mn) 0.6 Fe 0.4 PO4, 195g of lithium carbonate, 17.7g of niobium pentoxide (Nb2O5), and 3200mL of deionized water were added. After mixing, the mixture was sent to a sand mill for grinding to obtain a uniform slurry. Steps 2 to 6 are the same as steps 2 to 6 in Example 1.
[0067] Comparative Example 5: A method for preparing a lithium iron manganese phosphate cathode material includes the following steps: Step 1, Precursor Mixing and Milling: Weigh 1000g of manganese iron phosphate (Mn) 0.6 Fe 0.4 PO4, 195g of lithium carbonate, and 100g of glucose as a carbon source were added, along with 2700mL of deionized water. The mixture was then fed into a sand mill for grinding to obtain a uniform slurry. Steps 2 to 6 are the same as steps 2 to 6 in Example 1.
[0068] Lithium manganese iron phosphate cathode material, acetylene black, and PVDF were mixed in a mass ratio of 8:1:1, and an appropriate amount of NMP was added. The mixture was stirred into a paste, coated onto aluminum foil, and dried to form the cathode sheet. A lithium metal sheet was used as the anode, and a polypropylene porous membrane was used as the separator. 2023-type button batteries were assembled in a glove box. The assembled batteries underwent constant current charge-discharge testing within a voltage range of 2.5~4.5V. The first three cycles were at a rate of 0.1C, followed by a rate of 1C, for a total of 300 cycles. The initial discharge capacity and capacity retention of the prepared lithium manganese iron phosphate battery were measured.
[0069] The positive electrode material is pressed into a dense disc under high voltage, and then four equidistant probes are pressed onto the same side surface. A constant current is passed through the two outer probes, and the voltage drop is measured by the two inner probes. This eliminates the interference of the contact resistance of the wires and probes. Finally, the electronic conductivity is calculated based on the thickness and area of the disc.
[0070] The test results are shown in Table 1.
[0071] Table 1 Performance data of batteries assembled from the cathode materials prepared in Examples 1-3 and Comparative Examples 1-5 As shown in Table 1, the cathode materials prepared in Examples 1-3 possess excellent discharge capacity, electronic conductivity, and cycle stability. This invention optimizes the crystal lattice structure through multi-element cation doping, improving lithium-ion transport kinetics. It also synergistically constructs a highly efficient electronic conductivity network through inner carbon coating. Simultaneously, the surface magnesium silicate and magnesium aluminum silicate composite coating structure stabilizes the electrode interface, and residual lithium carbonate on the material surface can react with silicates in situ to form lithium-silicate, further reducing interface impedance. The double-layer coating and synergistic lattice modification significantly suppress transition metal dissolution and electrolyte side reactions during cycling, effectively maintaining the integrity of the crystal structure. This results in excellent overall conductivity, full capacity utilization, stable long-cycle performance, and optimal comprehensive electrochemical performance.
[0072] Comparative Example 1 is a pure-phase lithium iron manganese phosphate material without doping or coating modification. Without any structural optimization or interface protection, the material has poor intrinsic electronic conductivity, high lithium-ion transport resistance, and its crystal structure is prone to distortion and collapse during charge and discharge. Manganese ion dissolution is severe, and electrolyte side reactions are continuously aggravated, resulting in poor capacity utilization, low electronic conductivity, and significantly deteriorated cycle performance. The overall electrochemical performance is the worst, which fully demonstrates that modification methods play a decisive role in improving the electrochemical performance of lithium iron manganese phosphate.
[0073] Comparative Example 2 only used single carbon coating modification, without cationic lattice doping and silicate coating modification. Compared with the pure phase material, its performance was slightly improved, but the overall performance was still relatively poor. Single carbon coating can only slightly improve the surface electronic conductivity of the material, but it cannot optimize the bulk lattice structure, effectively suppress manganese ion dissolution and interfacial side reactions. The structural stability of the material is insufficient during long-term cycling, and the capacity decay rate is relatively fast. It is difficult to achieve both excellent conductivity and long-term cycling stability, and the modification effect has obvious limitations.
[0074] Comparative Example 3 only underwent cation lattice doping modification, without constructing a carbon coating and silicate protective layer. Lattice doping can effectively optimize the internal crystal structure of the material, improve ion transport capability, and slightly enhance the material's conductivity and structural stability. However, the material surface lacks an effective interfacial protective layer, allowing the electrolyte to directly corrode the active matrix. During cycling, there are still significant problems with metal ion dissolution and interfacial degradation, resulting in limited improvement in cycling performance. Overall, the electrochemical performance is significantly weaker than the synergistically modified sample with dual coating in this invention.
[0075] Comparative Example 4 uses cation doping combined with single-layer carbon coating modification, without an outer silicate coating layer. Compared with the single-modification sample, its performance is further improved, exhibiting relatively better conductivity and basic cycling performance. However, due to the lack of an outer silicate protective structure, it cannot effectively block electrolyte corrosion and inhibit manganese ion dissolution in the long term. During long-term cycling, the electrode interface stability is insufficient, and the capacity decay is relatively significant. The cycling stability still has obvious shortcomings, and its overall performance is inferior to the double-layer composite coating modified material of this invention.
[0076] Comparative Example 5 uses cation doping combined with monolayer silicate coating modification, without an inner carbon conductive layer. Silicate coating can effectively block the electrolyte from contacting the active material, inhibit metal ion dissolution, and improve the material's cycling stability. However, silicate itself has weak conductivity, and without the synergistic support of a highly conductive carbon network, the overall electronic conductivity of the material is poor, the interface impedance is high, the capacity utilization is limited, and there are obvious defects in rate capability and conductivity. This proves that the inner carbon coating and the outer silicate coating are complementary and indispensable synergistic modification structures.
[0077] The test data provided in Table 1 indirectly confirms that the embodiments of the present invention have superior rate charge-discharge performance: the initial discharge capacity of embodiments 1-3 at 0.1C is significantly higher than that of comparative embodiments 1-5, demonstrating stronger reversibility of lithium-ion insertion / extraction and smaller initial polarization during charge-discharge; secondly, the electronic conductivity of the embodiments is increased by 2-5 orders of magnitude compared with the comparative embodiments, relying on the carbon-coated conductive network to eliminate the intrinsic electronic conductivity shortcomings of lithium iron manganese phosphate, ensuring rapid electron transport under high current charge-discharge; at the same time, the outer silicate coating significantly reduces the amount of manganese ion dissolution during cycling, avoiding the problem of excessive SEI film thickening and continuous increase in interface impedance caused by transition metal ion deposition; in addition, the capacity retention rate of 300 long cycles at 1C rate is higher than 98%, indicating that the material structure has good stability and weak cycle polarization increment during repeated charge-discharge at high rates. Multiple sets of quantitative data jointly confirm that the lithium-ion and electron conduction kinetics of the embodiments are better, and the rate performance is significantly better than that of the comparative samples without doping, carbon coating, or outer silicate coating.
[0078] The above-described embodiments are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the technical scope of the present invention, based on the technical solution and concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A lithium iron manganese phosphate cathode material, characterized in that, It includes a matrix, a first coating layer, and a second coating layer, wherein the general chemical formula of the matrix is LiFe. 1-x-y Mn x M y PO4, 0.5≤x≤0.9, 0.02≤y≤0.05, M is any one or more of W, Mo, Nb, V, Ti, and Zr; The first coating layer covers at least a portion of the surface of the substrate, and the first coating layer is carbon. The second coating layer covers at least a portion of the surface of the particles formed by the matrix and the first coating layer, and the second coating layer is any one or both of magnesium metasilicate and magnesium aluminum silicate.
2. The lithium iron manganese phosphate cathode material as described in claim 1, characterized in that, The mass ratio of the first coating layer to the substrate is (0.8%~2.5%):1; The mass ratio of the second coating layer to the substrate is (0.5%~5%):
1.
3. A method for preparing a lithium iron manganese phosphate cathode material, characterized in that, Includes the following steps: Step 1: Mix manganese iron phosphate, lithium source, M cation source, deionized water and carbon source, and mill to obtain a mixture; Step 2: Spray dry the mixture to obtain precursor powder; Step 3: Heat-treat the precursor powder under an inert atmosphere to obtain cation-doped lithium manganese iron phosphate material. Step 4: Disperse the cation-doped lithium manganese iron phosphate material in deionized water to obtain a suspension; Step 5: Add metal salt to the suspension and heat in a water bath, then add sodium silicate solution dropwise and simultaneously add ammonia water for stirring and reaction, then let it settle, wash and vacuum dry in sequence to obtain the intermediate product; Step 6: Heat-treat the intermediate product under an inert atmosphere to obtain the lithium iron manganese phosphate cathode material.
4. The method for preparing lithium iron manganese phosphate cathode material as described in claim 3, characterized in that, In step 1, the lithium source is any one or more of lithium carbonate, lithium hydroxide, and lithium oxalate; The M element in the M cation source is any one or more of W, Mo, Nb, V, Ti, and Zr; The M cation source is a metal oxide; the carbon source is any one or more of glucose, sucrose, and citric acid.
5. The method for preparing lithium iron manganese phosphate cathode material as described in claim 3, characterized in that, In step 1, the ratio of the sum of the molar amounts of manganese and iron in ferromanganese phosphate to the molar amount of lithium in the lithium source is 1: (1.02~1.08). The molar ratio of element M in the M cation source to element lithium in the lithium source is (2%~5%):1; The mass ratio of carbon source to manganese iron phosphate is (5%~20%):1; The solid content in the mixture is 20wt%~40wt%.
6. The method for preparing lithium iron manganese phosphate cathode material as described in claim 3, characterized in that, Step 3: The heat treatment temperature is 600~750℃, the heat treatment time is 8~24h, and the heating rate is 2~5℃ / min; In step 4, the solid content of the suspension is 10 wt.% to 25 wt.%.
7. The method for preparing lithium iron manganese phosphate cathode material as described in claim 3, characterized in that, In step 5, the metal salt is any one or both of magnesium salt and aluminum salt; The water bath heating temperature is 65~85℃; The equivalent silica mass fraction in the sodium silicate solution is 5 wt.%~10 wt.%; the dropping rate of the sodium silicate solution is 0.5~2 mL / min; When adding sodium silicate solution, ammonia water is added simultaneously to maintain the pH of the reaction system at 7.0~9.0, and the reaction is stirred continuously for 1~4 hours.
8. The method for preparing lithium iron manganese phosphate cathode material as described in claim 3, characterized in that, In step 6, the heat treatment temperature is 450~650℃, the heat treatment time is 2~6h, and the heating rate is 1~3℃ / min.
9. The method for preparing lithium iron manganese phosphate cathode material as described in claim 3, characterized in that, Step 6 is followed by cooling, crushing, and sieving. The undersize material is the finished lithium iron manganese phosphate cathode material.
10. A battery, characterized in that, The lithium iron manganese phosphate cathode material includes any one of claims 1 to 2 or any one of claims 3 to 9.